Transport and Golgi organisation protein 1 is a novel tumour progressive factor in oral squamous cell carcinoma - Sasahira, Tomonori; Kirita, Tadaaki; Yamamoto, Kazuhiko; Ueda, Nobuhiro; Kurihara, Miyako; Matsushima, Sayako; Bhawal, Ujjal K.; Bosserhoff, Anja Katrin; Kuniyasu, Hiroki (European Journal of Cancer, 2014)
Transport and Golgi organisation protein 1 (TANGO), also known as MIA3, belongs to the melanoma inhibitory activity (MIA) gene family. Although MIA acts as an oncogene, MIA2 and TANGO have a tumour-suppressive function in several malignancies; accordingly, the role and function of the MIA gene family in tumours remain controversial. Here the roles of TANGO were investigated in oral squamous cell carcinoma (OSCC). We analysed expression and function of TANGO in human OSCC cell lines. TANGO expression was also examined in 171 cases of primary OSCC by immunohistochemistry and statistically assessed the correlation between TANGO positivity and the clinicopathological parameters including vessel density. By TANGO knockdown in OSCC cells, the growth and invasion were repressed and apoptosis was induced. Activities of platelet-derived growth factor beta polypeptide (PDGFB) and Neuropilin2 were inhibited by TANGO knockdown. TANGO immunoreactivity was detected in 35.1% (60/171) cases of OSCC. TANGO expression was strongly associated with tumour progression, nodal metastasis, clinical stage and number of blood or lymph vessels in OSCC. Patients showing TANGO-expression fared significantly worse disease-free survival than cases without TANGO expression. These findings suggest that TANGO might promote angiogenesis and lymphangiogenesis by upregulation of PDGFB and Neuropilin2 in OSCC. © 2014 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiogenesis; Lymphangiogenesis; MIA; Neuropilin2; Oral cancer; PDGFB; TANGO